2005
DOI: 10.1097/00004872-200501000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin B2 receptor gene (???58T/C) polymorphism influences baroreflex sensitivity in never-treated hypertensive patients

Abstract: B2R genotype can explain part of the BRS variation that is unaccounted for by simple anthropometric variables and common risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…On the other hand, BK acting through B 2 and atypical receptors is involved in central mechanisms of cardiovascular regulation, and its cardioinhibitory effect may be attributed to deregulation of the autonomic control of the heart rhythm. 13,14 In the in vitro uterus assay, compounds III and VII exhibited negligible agonistic properties, while their acylated counterparts IV and VIII were inactive. Peptides I, II, V, and VI showed varying degrees of antagonistic activity ranging from very low antagonism (pA 2 ≈ 5.5) to rather potent antagonism (pA 2 ) 7.4).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, BK acting through B 2 and atypical receptors is involved in central mechanisms of cardiovascular regulation, and its cardioinhibitory effect may be attributed to deregulation of the autonomic control of the heart rhythm. 13,14 In the in vitro uterus assay, compounds III and VII exhibited negligible agonistic properties, while their acylated counterparts IV and VIII were inactive. Peptides I, II, V, and VI showed varying degrees of antagonistic activity ranging from very low antagonism (pA 2 ≈ 5.5) to rather potent antagonism (pA 2 ) 7.4).…”
Section: Resultsmentioning
confidence: 99%
“…It has been well recognized that BRS is impaired in hypertensive humans and animals [22][23][24][25] . Accordingly, we demonstrated that the LH rats had lower BRS than the LL rats.…”
Section: Discussionmentioning
confidence: 99%
“…Most evidence suggests that BRS is partly influenced by genetic factors [4], and indeed previously identified polymorphisms seem to explain part of the variance in BRS [30,31]. However, until now only one study reported on the heritability of BRS, in that case obtained from 5-min measurements during a rest condition [5].…”
Section: Discussionmentioning
confidence: 99%